Exercise efficiency is reduced by mitochondrial uncoupling in the elderly. Issue 3 (23rd November 2012) - Conley, Kevin E.; Jubrias, Sharon A.; Cress, M. Elaine; Esselman, Peter
<x xml:space="preserve">Abstract</x> A reduction in exercise efficiency accompanies ageing in humans. Here we evaluated the impact of changes in the contractile‐coupling and mitochondrial‐coupling efficiencies on the reduction in exercise efficiency in the elderly. Nine adult (mean, 38.8 years old) and 40 elderly subjects (mean, 68.8 years old) performed a cycle ergometer test to measure O2 uptake and leg power output up to the aerobic limit (<inline-graphic xlink:href="ark:/27927/pgg3hkkx1w8" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />). Reduced leg power output per unit O2 uptake was reflected in a drop in delta efficiency (ɛD) from 0.27 ± 0.01 (mean ± SEM) in adults to 0.22 ± 0.01 in the elderly group. Similar declines with age were apparent for both the leg power output at <inline-graphic xlink:href="ark:/27927/pgg3hkkx22j" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> and the ATP generation capacity (ATPmax) determined in vivo using 31P magnetic resonance spectroscopy. These similar declines resulted in unchanged contractile‐coupling efficiency values (ɛC) in the adult (0.50 ± 0.05) versus the elderly group (0.58 ± 0.04) and agreed with independent measures of muscle contractile‐coupling efficiency in human quadriceps (0.5). The mitochondrial‐coupling efficiency calculated from the ratio of delta to contractile‐coupling efficiencies in the adults (ɛD/ɛC= 0.58 ± 0.08) corresponded to values for well‐coupled mitochondria (0.6); however, ɛD/ɛC was significantly lower in the elderly subjects (0.44 ± 0.03). Conversion of ATPmax per mitochondrial volume (ATPmax/Vv[mt, f]) reported in these groups into thermodynamic units confirmed this drop in mitochondrial‐coupling efficiency from 0.57 ± 0.08 in adults to 0.41 ± 0.03 in elderly subjects. Thus, two independent methods revealed that reduced mitochondrial‐coupling efficiency was a key part of the drop in exercise efficiency in these elderly subjects and may be an important part of the loss of exercise performance with age.